Kajian Bibliometrik Riset Minyak Dan Gas Bumi Nasional 1990-2014 - Himawanto, Himawanto (Program Studi Ilmu Perpustakaan UIN Alauddin, 2015)
Abstrak : Ketergantungan tinggi pendapatan nasional atas minyak dan gas bumi memicu pemroduksian pada tingkat maksimal yang mengakibatkan cadangan migas menurun drastis sehingga muncul respon dikalangan peneliti untuk menemukan metode atau konsep baru inovatif. Dalam usaha menyebarluaskan konsep inovatif para peneliti tersebut kepada masyarakat, Lemigas sebagai pusat riset menerbitkan Jurnal Scientific Contribution Oil and Gas. Kurun waktu 1990-2014 riset migas yang terekam berjumlah 336 artikel. Fokus utama peningkatan cadangan dan produksi migas terbanyak diteliti hingga 41.07%, disusul topik riset proses sebanyak 25.89% bertujuan mengurangi ketergantungan pada minyak. Riset dikerjakan peneliti dari delapan negara yang geografisnya berada pada enam wilayah regional atau tiga benua. Menurut aspirasi wawasan 112 peneliti dari dua benua berkontribusi menghasilkan artikel, dan sebagiannya bereputasi global dengan terindeks di Scopus. Sebanyak dua hingga empat peneliti lebih yang berafiliasi dari delapan jenis institusi di Asia, Eropa, dan Amerika berkolaborasi menghasilkan 154 produk riset. Selama hampir tiga dekade kerjasama riset migas berfluktuasi dan periode 2010-2014 tingkat kolaborasinya semakin meningkat.Kata Kunci: Bibliometrik, Fokus riset, Aspirasi wawasan, KolaborasiÂ Abstract : High dependence of national income on oil and natural gas fueled production at the maximum level which results in oil and gas reserves dropped dramatically so that it appears response among researchers to find innovative methods or new concepts. In order to accommodate researchers to account for its innovative concept and disseminate to the public, Lemigas as a research center publishes the journal Scientific Contribution Oil and Gas. To know the main focus, insights and aspirations of active contributors, as well as the approach taken bibliometric research collaboration. The period 1990-2014 recorded oil and gas research amounted to 336 articles. The main focus of the increase in oil and gas reserves and production of the most studied up to 41.07%, followed by the research topic as much as 25.89% process aims to reduce dependence on oil. Research carried researchers from eight countries are in the six geographical region or three continents. According to the aspirations of insight 112 researchers from two continents contribute to produce the article, and partly repute global. As many as two to four more investigators affiliated from eight types of institutions in Asia, Europe, and the United States collaborated to produce 154 research products. For nearly three decades of fluctuating oil and gas research cooperation and the 2010-2014 period increased level of collaboration.Key Words: Bibliometrics, Research focus, Insight aspiration, CollaborationÂ